Testimonio as counter-propaganda: a comparative analysis of Latin-American women's testimonial literature - Mason, Sofia Sandina Maniscalco (2014)
This thesis creates a gendered typology of women’s testimonio that foregrounds the Cold War context of the genre. This new perspective reveals that contrary to the assertions of some critics, the texts struggle to convey a unitary propagandic message. Rather, their prime purpose is to counter hegemonic discourse. Yet, far from being unliterary or impersonal, they impart much personal information using a diversity of stylistic devices.